1997
DOI: 10.1074/jbc.272.40.25238
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Undergoes Phosphorylation by c-Jun N-terminal Kinase/Stress-activated Protein Kinases in the Presence of the Constitutively Active GTP-binding Protein Rac1

Abstract: We have studied the phosphorylation of the Bcl-2 family of proteins by different mitogen-activated protein (MAP) kinases. Purified Bcl-2 was found to be phosphorylated by the c-Jun N-terminal kinase/stress-activated protein kinase (JNK/SAPK) p54-SAPK␤, and this is specific insofar as the extracellular signal-regulated kinase 1 (ERK1) and p38/RK/CSBP (p38) catalyzed only weak modification. Bcl-2 undergoes similar phosphorylation in COS-7 when coexpressed together with p54-SAPK␤ and the constitutive Rac1 mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
271
3
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(289 citation statements)
references
References 35 publications
13
271
3
2
Order By: Relevance
“…One report suggests that JNK can directly inactivate Bcl-2 by phosphorylation of one or all of four serine and threonine residues within the¯exible loop that resides N-terminal to the BH3 domain (Maundrell et al, 1997). Consistent with this hypothesis in WEHI-231 B cells, full-length Bcl-2 is hyperphosphorylated and ine ective in preventing anti-IgM-induced death while a loop-deletion mutant blocked apoptosis.…”
Section: Targets For Jnk Signaling Of Apoptosismentioning
confidence: 80%
“…One report suggests that JNK can directly inactivate Bcl-2 by phosphorylation of one or all of four serine and threonine residues within the¯exible loop that resides N-terminal to the BH3 domain (Maundrell et al, 1997). Consistent with this hypothesis in WEHI-231 B cells, full-length Bcl-2 is hyperphosphorylated and ine ective in preventing anti-IgM-induced death while a loop-deletion mutant blocked apoptosis.…”
Section: Targets For Jnk Signaling Of Apoptosismentioning
confidence: 80%
“…JNK has been implicated in the implementation of programmed cell death in response to a variety of stressful stimuli, but the downstream e ectors involved in mediating its apoptotic e ects have not been identi®ed. A recent report demonstrated that JNK was capable of phosphorylating Bcl-2 (Maundrell et al, 1997), suggesting the possibility that JNK could play a role in Taxol-induced Bcl-2 phosphorylation. However, our ®nding that TPCK did not a ect the level of JNK activity seen in response to Taxol treatment although it completely prevented Bcl-2 phosphorylation, argue against this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 survival proteins are known to be inhibited by JNK. [58][59][60][61] In the case of Bcl-2 and Mcl-1, JNK inactivates these survival factors by direct phosphorylation. 24,62 However, ZBP-89 expression had no effect on Bcl-2.…”
Section: Ibmentioning
confidence: 99%